Mechanical, thermooxidative and biodegradable properties of composites from epoxyurethanes and chemically modified hemp woody core - T. F. Samoilenko; L. M. Yashchenko; N. V. Yarova; O. O. Leta; O. O. Brovko (Хімія, фізика та технологія поверхні)
Natural fibre reinforced polymer composites nowadays are considered to be attractive cheap, safe and eco-friendly materials. The main problem of such composites related to the hydrophilicity of plant fibres may be successfully solved by chemical modification of their surface. However, some characteristics of the materials may be suppressed after this procedure. Therefore, the aim of the research is to find out the impact of chemical modification of filler on thermooxidative stability, tensile and flexural strength, as well as on biodegradability of polymer composites. The novelty of this work is in the examining new materials on the basis of Si-containing epoxyurethanes and chemically treated hemp woody core (HWC). Woody core that is the side product of hemp industry requiring its apropriate utilization was exposed to mercerization with sodium hydroxide solution and to further functionalization with epoxidized soybean oil (ESO) or 3-aminopropyltriethoxysilane (APS). Raw and surface treated HWC was used as reinforcement for two types of organic-inorganic epoxyurethane matrices made from sodium silicate, polyurethane prepolymer based on polyisocyanate and castor oil, and either diglycidyl ether of bisphenol-A (DGEBA) or ESO as epoxy component.